Political Change and Informality: Evidence from the Arab Spring - Ahmed Elsayed; Jackline Wahba (Institute of Labor Economics (IZA), 2017)
This paper examines informality during the political and economic turmoil that accompanied the Arab Spring revolution in Egypt. The paper focuses on unprotected employment and the extent to which it changed by educational level right after the January Uprising of 2011. We find that over time and particularly after the revolution, informal employment has increased for both high- and low-educated workers however, through different paths: high educated were more likely to be stuck in informality, whilst low-educated formal workers were more likely to lose their contracts. The results suggest a high level of rigidity in the Egyptian labor market even in the wake of the Arab Spring.
Keywords: J21; J23; J24; J31; O17; 330; informal employment; job contracts; Arab Spring